Long-term use and tolerability of irbesartan for control of hypertension - Forni, Valentina (Dove Medical Press, 2011)
In this review, we discuss the pharmacological and clinical properties of irbesartan, a noncompetitive angiotensin II receptor type 1 antagonist, successfully used for more than a decade in the treatment of essential hypertension. Irbesartan exerts its antihypertensive effect through an inhibitory effect on the pressure response to angiotensin II. Irbesartan 150–300 mg once daily confers a lasting effect over 24 hours, and its antihypertensive efficacy is further enhanced by the coadministration of hydrochlorothiazide. Additionally and partially beyond its blood pressure-lowering effect, irbesartan reduces left ventricular hypertrophy, favors right atrial remodeling in atrial fibrillation, and increases the likelihood of maintenance of sinus rhythm after cardioversion in atrial fibrillation. In addition, the renoprotective effects of irbesartan are well documented in the early and later stages of renal disease in type 2 diabetics. Furthermore, both the therapeutic effectiveness and the placebo-like side effect profile contribute to a high adherence rate to the drug. Currently, irbesartan in monotherapy or combination therapy with hydrochlorothiazide represent a rationale pharmacologic approach for arterial hypertension and early-stage and late-stage diabetic nephropathy in hypertensive type II diabetics.